Consumerism Behavior in Gaming Live Streaming: A Comparative Study of Subscription-Gifting Among YouTube Gaming Viewers in Indonesia and Douyu Viewers in China - Rahmi, Lutfia Fatihah; Koesoemadinata, Mohammad Isa Pramana; Rahman , Yanuar (International Journal Labs, 2025)
This study aims to analyze consumer behavior in live streaming, focusing on gift-giving behavior on YouTube Gaming in Indonesia and Douyu in China. Using a descriptive qualitative approach, this research explores the influence of parasocial presence (PSR) and social presence (SP) on viewers’ decisions to gift to streamers. The study also conducts a comparative analysis with previous research on Douyu to identify similarities and differences in audience behavior. The findings indicate that although PSR influences gift-giving behavior, its effect is stronger on YouTube Gaming than on Douyu, where higher donation amounts are observed. These results contribute to the understanding of the evolution of digital culture, particularly regarding consumerism in new media, and its global cultural relevance.